TP53 Status is Associated with Thrombospondin1 Expression In vitro - Alvarez Secord, Angeles; Bernardini, Marcus Q.; Broadwater, Gloria; Grace, Lisa A.; Huang, Zhiqing; Baba, Tsukasa; Kondo, Eiji; Sfakianos, Gregory; Havrilesky, Laura J.; Murphy, Susan K. (Frontiers in Oncology, 2013)
Objectives: To elucidate the association between thrombospondin1 (THBS1) expression and TP53 status and THBS1 promoter methylation in epithelial ovarian cancer (EOC). Methods: Epithelial ovarian cancer cell lines with known TP53 status were analyzed for THBS1 gene expression using Affymetrix U133 microarrays and promoter methylation by pyrosequencing. THBS1 mRNA expression was obtained pre- and post-exposure to radiation and hypoxia treatment in A2780 parent wild-type (wt) and mutant (m)TP53 cells. THBS1 expression was compared to tumor growth properties. Results:THBS1 gene expression was higher in cells containing a wtTP53 gene or null TP53 mutation (p = 0.005) and low or absent p53 protein expression (p = 0.008) compared to those harboring a missense TP53 gene mutation and exhibiting high p53 protein expression. Following exposure to radiation, there was a 3.4-fold increase in THBS1 mRNA levels in the mTP53 versus wtTP53 A2780 cells. After exposure to hypoxia, THBS1 mRNA levels increased approximately fourfold in both wtTP53 and mTP53 A2780 cells. Promoter methylation levels were low (median = 8.6%; range = 3.5–88.8%). There was a non-significant inverse correlation between THBS1 methylation and transcript levels. There was no association between THBS1 expression and population doubling time, invasive capacity, or anchorage-independent growth. Conclusion:THBS1 expression may be regulated via the TP53 pathway, and induced by hypoxic tumor microenvironment conditions. Overall low levels of THBS1 promoter methylation imply that methylation is not the primary driver of THBS1 expression in EOC.